The Influence of Learning Styles and Student Creativity on Learning Outcomes: Pengaruh Gaya Belajar dan Kreativitas Siswa terhadap Hasil Belajar - Baihaqi, Baihaqi; Umasangadji, Fahmi; Siburian, Saidal; Nurmala, Eka; Muhammad, Fadel (PT. Alpha Trianguli Australis, 2025)
Education plays a very important role in shaping the quality of superior human resources. Learning outcomes are the main indicator used to assess the effectiveness of learning. With the increasing development of technology and paradigm shifts in the world of education, it is important for educators to understand the dynamics of learning styles and creativity in learning. This study uses the Systematic Literature Review (SLR) approach to collect, evaluate, and analyze previous research related to the influence of students' learning styles and creativity on learning outcomes. The results of this study are: 1) Learning styles and creativity have a significant influence on student learning outcomes; 2) Educators must understand the variations in students' learning styles and provide flexible and innovative teaching strategies; and 3) A learning environment that supports exploration and innovation is very important in enhancing student creativity.